Kinds, things, and stuff mass terms and generics - Pelletier, Francis Jeffry; Carlson, Greg; Gelman, Susan A.; Goddard, Cliff; Hampton, James A.; Pelletier, Francis Jeffry; Prasada, Sandeep; Wisniewski, Edward J.; Xu, Fei (New directions in cognitive science, 2010)
With philosophical and linguistic semanticists on the one side and cognitive and developmental psychologists on the other, questions in the semantic and logical theories of generic statements that employ mass terms by looking to the cognitive abilities of speakers and of child language-learners are discussed.